THE POLITENESS EXPRESSIONS IN USING INDONESIAN IN THE CLASSROOM VERBAL INTERACTION A STUDY CASE AT THE HOSPITALITY BUSINESS MANAGEMENTSTUDENTS OF TOURISM FACULTY OF TRIATMA MULYA UNIVERSITY BALI - Anggreni, Ni Putu Yunik; Rai Antara, I Made Agung (Akademi Komunitas MAPINDO, 2021)
The use of speech act cannot be separated from our daily life, an example of it is in the verbal interaction in classroom learning. Students use speech acts in classroom to convey messages such as to express politeness. This study aimed to find out (1) the expression forms and (2) the delivering strategies of Indonesian speech act politeness of the students of Hospitality Business Management of Triatma Mulya University Bali in the verbal interaction in the teaching and learning process of Indonesian subject. The sample was 35 students of Hospitality Business Management of Triatma Mulya University who were taking Indonesian subject. The data were analyzed using a descriptive qualitative method by employing a communication ethnography design. The findings show that the students’ politeness forms of speech act in using Indonesian can be expressed in forms of declarative, interrogative, and imperative modes, while (2)the students politeness strategies are expressed in forms of direct and indirect speech act strategies. Keywords: Politeness expression, politeness strategies, verbal interaction, speech acts.